2010
DOI: 10.1111/j.1529-8817.2010.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Phylogenetic and Geometric Morphometric Evaluation of Micrasterias Crux-Melitensis/M. Radians Species Complex1

Abstract: We investigated nine strains of the Micrasterias crux-melitensis (Ehrenb.) Hassall ex Ralfs and M. radians W. B. Turner species complex. A combination of molecular, morphological, and geometric morphometric data was used to reveal the patterns of their phenotypic and phylogenetic differentiation. The molecular data based on internal transcribed spacer (ITS) rDNA, glycine transfer RNA (trnG uuc ) intron, and SSU rDNA sequences revealed three phylogenetic lineages. One of them comprised the six European and Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…This has also been concluded by other authors (e.g. coesel 1984; Gontcharov et al 2002;neustupa et al 2010) and its full potential obviously hasn't been realized yet. This especially concerns smaller forms with few morphological characteristics where it may be used for the delimitation of (pseudo)cryptic species.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…This has also been concluded by other authors (e.g. coesel 1984; Gontcharov et al 2002;neustupa et al 2010) and its full potential obviously hasn't been realized yet. This especially concerns smaller forms with few morphological characteristics where it may be used for the delimitation of (pseudo)cryptic species.…”
Section: Discussionsupporting
confidence: 62%
“…This trend has been convincingly demonstrated in several recent papers (e.g. neustupa et al 2010, 2011neMjová et al 2011). In our opinion, it can be assumed that the estimation of the overall global desmid species number by hoshaw et al (1990, 15000 spp.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Genbank data of a M. crux-melitensis strain from the Japanese NIES culture collection, however, showed a closer affiliation with M. radians var. evoluta than with the analyzed strains of European/North American M. crux-melitensis (Neustupa et al 2010). Photographs of the strain NIES-152 indicate that this strain morphologically is more similar to M. radians than to M. crux-melitensis, suggesting a possible misidentification (National Institute for Environmental Studies 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This could better explain the gradual transition found by those authors between 'typical' M. radians in tropical lowland waters and their supposed M. crux-melitensis in high altitude Papua New Guinea lakes. Interestingly, Neustupa et al (2010) based on molecular data found some six European and North American strains of M. crux-melitensis to belong to another phylogenetic lineage than two Kenia strains of M. radians var. evoluta.…”
Section: Discussionmentioning
confidence: 99%